Relationships of Ischemic Stroke Occurrence and Outcome with Gene Variants Encoding Enzymes of Tryptophan Metabolism - Fanni Annamária Boros; Rita Maszlag-Török; Mónika Szűcs; Ádám Annus; Péter Klivényi; László Vécsei (Biomedicines, 2021)
Ischemic stroke is among the leading causes of mortality and long-term disability worldwide. Among stroke risk factors the importance of genetic background is gaining interest. There is a growing body of evidence of changes of metabolite levels and enzyme activities involved in the conversion of Trp during the course of cerebral ischemia. We compared the frequencies of ten SNPs of five genes related to Trp metabolism between groups of 122 ischemic stroke patients and 120 control individuals. Furthermore, we examined the mRNA levels of TPH1, IDO1 and KYAT1 genes in peripheral venous blood with the aim of assessing (i) whether there are changes in their expression during the course of stroke and (ii) does any of their investigated SNPs have an impact on gene expression. In seven cases out of ten studied polymorphisms we detected significant differences in frequencies in relation to ischemic stroke occurrence, etiology, and clinical parameters. We also detected changes in the expression of TPH1 and IDO1 genes during the course of the disease. We found that those IDO1 variants which show a trend towards elevated mRNA level are more frequent in stroke patients than in controls. Our results are important novel observations which suggest a causal relationship between elevated IDO1 expression and stroke etiology.